Estimating the burden of arboviral diseases in Colombia between 2013 and 2016 (2020)
Objective: During the 2013–2016 period, Dengue, Chikungunya, and Zika affected more than 1 million people in Colombia. These arboviruses and their chronic manifestations pose a public health challenge. Therefore, we estimated the burden of disease by Dengue, Chikungunya, and Zika in Colombia between 2013 and 2016. Methods: An exploratory ecological study was carried out using the disability-adjusted life years (DALYs) as a unit of measure. The mortality databases of the National Administrative Department of Statistics (DANE) and the morbidity databases of the National Public Health Surveillance System (SIVIGILA) were used. Deaths and cases for each arbovirus were grouped and then adjusted to control biases. Subsequently, we performed a sensitivity analysis. Results: In the 2013–2016 period, 491,629.2 DALYs were lost due to arboviruses in Colombia. By disease, 26.6% of the total DALYs were caused by Dengue, 71.3% by Chikungunya, and the remaining 2.2%, by Zika. The majority of DALYs (68.2%) were caused by chronic complications. Five out of 32 departments (Valle del Cauca, Tolima, Norte de Santander, Huila, and Bolívar) contributed 50.5% of total DALYs. Conclusion: The burden of disease by arboviruses in the 2013–2016 period exceeded the burden of other infectious diseases such as HIV/AIDS and tuberculosis in Colombia. Public health efforts must be made to mitigate new epidemics of these arboviruses.